Bowen disease - clinic, dermoscopy, patology - Poklękowska Katarzyna; Brzeziński Piotr (Our Dermatology Online, 2011)
Bowen Disease is squamous cell carcinoma in situ in which the basement membrane is intact on histopathology. Lesions are usually solitary but may be multiple in 10-20 percent of cases. It typically presents as an erythematous enlarging plaque having irregular borders with scaling and crusting. The lesions may be fissured or verrucous or, rarely, pigmented. Ulceration may occur and is often a sign that invasive disease is developing. The risk of progression of Bowen disease to invasive carcinoma is about 3%. Bowen disease is most commonly found in patients over 60 years old. Oher risk factors: include chronic sun exposure, immunosuppression, arsenic exposure and cutaneous human papillomavirus (HPV- 16, 18, 34 i 48) infection.The majority of cases of Bowen disease revealed a peculiar dermoscopic pattern characterized by glomerular vesselsProliferation of numerous atypical keratinocytes throughout the entire thickness of the epidermis with hyperkeratosis, mitotic figures, multinucleated cells and dyskeratotic cells, full thickness dysplasia of the squamous epithelum, disorderly maturation of the epidermis, parakeratosis and loss of granular layer.